Implementasi Pembiayaan Murabahah pada Baitul Mal Wat Tamwil (BMT) Kota Pekanbaru - Ficha Melina; Marina Zulfa (COSTING : Journal of Economic, Business and Accounting, 2020)
The rise of banking development using the principles of sharia, or better known as sharia banks or sharia microfinance institutions (LKMS) in Indonesia, is no longer a foreign matter. Research Objectives To find out how the implementation of Murabahah financing products in the BMT city of Pekanbaru, To find out whether the implementation of the Murabahah BMT contract in Pekanbaru is in accordance with Islamic principles. The method used is the total sampling method in which the population and sample numbered 22 people from the leadership of BMT or the Pekanbaru BMT financing department. Based on the results of this study that the Implementation of Murabahah Financing Products at BMT Pekanbaru City in the form of murabaha Objects, Cost and Profit, Cost, Advance, Purchase and Delivery of Goods, Resilient Payment, are very much in demand by customers and the public. It can be seen that there are many BMTs in the city of Pekanbaru that apply murabahah financing products that are principled to Muamalah in Islam. So that customers / communities are more interested in murabaha financing products than other products, and this financing is in accordance with Islamic Sharia principles. Keywords: Implementation, Financing, Murabahah, BMT Pekanbaru City